Probability methods for cost uncertainty analysis a systems engineering perspective - Garvey, Paul R., 1956-; Book, Stephen A.; Covert, Raymond P. (CRC Press, 2016)
Probability Methods for Cost Uncertainty Analysis: A Systems Engineering Perspective, Second Edition gives you a thorough grounding in the analytical methods needed for modeling and measuring uncertainty in the cost of engineering systems. This includes the treatment of correlation between the cost of system elements, how to present the analysis to decision-makers, and the use of bivariate probability distributions to capture joint interactions between a system's cost and schedule.